Generation of Functional Hepatocytes from Human Adipose‐Derived MYC+ KLF4+ GMNN+ Stem Cells Analyzed by Single‐Cell RNA‐Seq Profiling. (11th September 2018) - Li, Hongling; Zhu, Li; Chen, Huimin; Li, Tangping; Han, Qin; Wang, Shihua; Yao, Xinglei; Feng, Hongli; Fan, Linyuan; Gao, Shaorong; Boyd, Richard; Cao, Xu; et al.
Abstract: Cell transplantation holds considerable promise for end‐stage liver diseases but identifying a suitable, transplantable cell type has been problematic. Here, we describe a novel type of mesenchymal stem cells (MSCs) from human adipose tissue. These cells are different from previously reported MSCs, they are in the euchromatin state with epigenetic multipotency, and express pluripotent markers MYC, KLF4, and GMNN. Most of the genes associated with germ layer specification are modified by H3K4me3 or co‐modified by H3K4me3 and H3K27me3. We named this new type of MSCs as adult multipotent adipose‐derived stem cells (M‐ADSCs). Using a four‐step nonviral system, M‐ADSCs can be efficiently Induced into hepatocyte like cells with expression of hepatocyte markers, drug metabolizing enzymes and transporters, and the other basic functional properties including albumin (ALB) secretion, glycogen storage, detoxification, low‐density lipoprotein intake, and lipids accumulation. In vivo both M‐ADSCs‐derived hepatoblasts and hepatocytes could form vascularized liver‐like tissue, secrete ALB and express metabolic enzymes. Single‐cell RNA‐seq was used to investigate the important stages in this conversion. M‐ADSCs could be converted to a functionally multipotent state during the preinduction stage without undergoing reprogramming process. Our findings provide important insights into mechanisms underlying cell development and conversion.Stem Cells Translational Medicine 2018;7:792–805 Abstract : (A) The process of specialization of multipotent adipose‐derived stem cells (M‐ADSCs) to liver cells was speculated that will go through the activation, specialization, and maturation stages. (B) The single‐cell RNA‐seq was used to examine the underlying molecular mechanisms during hepatic differentiation and identified important events. (C) The schematic shows the actual differentiation pattern of M‐ADSCs conversion to hepatocyte like cells.